The Gossip - Bush, Nancy, 1953- (New York, NY : Zebra Books, Kensington Publishing Corp., 2021)
Mackenzie Laughlin, formerly with Oregons River Glen police department, has reluctantly agreed to investigate a local womans disappearance. The case reconnects her with Justin James Taft, a P.I. gifted at getting under Macs skin. But when the body is found tangled in river weeds, Mac and Taft realize that the case has changed, from one missing woman to a hunt for a terrifying and relentless killer...
Keywords: Murder -- Investigation; Fiction; Private investigators -- Fiction; Ex-police officers -- Fiction; Serial murders -- Fiction; Gossip -- Fiction; Babysitters -- Fiction; Oregon -- Fiction; Thrillers (Fiction); Romance fiction; Detective and mystery fiction